Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1993
DOI: 10.1063/1.109154
|View full text |Cite
|
Sign up to set email alerts
|

Raman scattering from diamond particles

Abstract: Raman spectra of diamond powders with size less than 2 μm have been measured as a function of the particle size. The Raman line was found to become more asymmetric with some tailing towards lower Raman shifts, broader, and weaker with decreasing particle size. The observed result can be explained by a phonon confinement effect rather than by a strain effect. This work predicts that it is very difficult to detect Raman spectra of diamond particles with size less than ∼50 Å. A broad Raman band, whose intensity b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
69
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(85 citation statements)
references
References 12 publications
15
69
0
1
Order By: Relevance
“…We optimized the size dependent Γ0 values by fitting the theoretical band shape with the experimental spectra. In agreement with previous studies [24,25] , Γ0 has been found to increase with decreasing the size (fig.4, dotted line). This tendency is well expected from stronger perturbations that a phonon experiences in smaller particles.…”
Section: Figsupporting
confidence: 81%
See 1 more Smart Citation
“…We optimized the size dependent Γ0 values by fitting the theoretical band shape with the experimental spectra. In agreement with previous studies [24,25] , Γ0 has been found to increase with decreasing the size (fig.4, dotted line). This tendency is well expected from stronger perturbations that a phonon experiences in smaller particles.…”
Section: Figsupporting
confidence: 81%
“…In the present work, we do not discuss the physical mechanisms involved in the homogeneous broadening as well as the analytical equation for it. We refrained from using the inverse size dependence of the dephasing constant Γ0 as suggested in the work [25] , because it gives unreasonably high Γ0 values as the size approaches the amorphous solid. We optimized the size dependent Γ0 values by fitting the theoretical band shape with the experimental spectra.…”
Section: Figmentioning
confidence: 99%
“…9 Another problem is to detect the "true" PSD averaged spectrum, rather than a local one (i.e., taken at one point). In previous works on ND, [10][11][12] the Raman measurements were mostly done for solid (powder) samples under a microscope. That makes the laser heating inevitable, and the PSD is detected at a particular point of the sample.…”
mentioning
confidence: 99%
“…However, for a material which contains both, amorphous and nanodiamond regions, or a hybrid combination of both, the two bands usually cannot be distinguished since the difference in location is only a few cm −1 . In addition, upon shrinking of the crystal to the nanoscale, major changes are observed in the Raman response of nanodiamonds: compared to bulk diamond, the nanodiamond peak is shifted to lower frequencies and appears broadened, sometimes with an asymmetry [89][90][91]. The phonon confinement effect is mainly considered as the physical origin for these changes [92].…”
Section: Discussionmentioning
confidence: 99%